Respuesta :
Answer:
p(x)=(x-7)(5x+1)(x-2)
Step-by-step explanation:
divide p(x) by (x-7) we got, 5x^2-9x-2
now it can further factoriesd as
5x^2-10x+x-2
=5x(x-2)+1(x-2)
=(5x+1)(x-2)
✌️:)
The rewrite p(x) as a product of linear factors p(x) =(x-7)(5x+1)(x-2).
Given that,
- The polynomial p(x) = [tex]5x^3 - 44x^2 + 61x + 14[/tex]has a known factor of (x – 7).
- We need to rewrite as a product of linear factors.
Based on the above information, the calculation is as follows:
Here we have to divide the (x - 7) from the given equation
Now if we divide it we get [tex]5x^2-9x-2[/tex].
Now we have to factor the above equation.
So,
= 5x(x-2) + 1(x-2)
= (5x+1)(x-2)
Therefore we can conclude that the rewrite p(x) as a product of linear factors p(x) =(x-7)(5x+1)(x-2).
Learn more: brainly.com/question/24169758